The Effect of Profitability, Leverage, and Firm Size on Earnings Quality with Independent Commissioners as Moderating Variable - Purnamasari, Eva; Fachrurrozie, Fachrurrozie (Accounting Analysis Journal, 2020)
This study aims to analyze the effect of profitability, leverage, and firm size on earnings quality with an independent commissioner as a moderating variable. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2016-2018. The sample selection uses a purposive sampling technique that produces a sample of 41 companies. The method used in this study is the documentation technique using secondary data derived from financial statements. The analytical tool used is Moderate Regression Analysis (MRA) with the help of SPSS software version 22. The results of this study indicate that profitability and firm size significantly have a positive effect on earnings quality. Meanwhile, leverage significantly has a negative effect on earnings quality. The effect of profitability and leverage on earnings quality cannot be moderated by independent commissioners. However, independent commissioners can only moderate the effect of firm size on earnings quality. The conclusion of this research is that companies can increase profitability and firm size and reduce the level of leverage to be able to produce quality profits by optimizing the proportion of independent commissioners in large companies. Keywords: Profitability; Leverage; Firm Size; Earnings Quality; Independent Commissioners